Types de chaînes de référence dans les articles de recherche de format IMRAD - Bruno Oberle (Discours)
Many research articles in experimental sciences present a standardized form known as the IMRAD format, an acronym for “Introduction, Methods, Results and Discussion”. Each of these sections has a specific purpose (presenting the framework, describing the methodology, reporting the results and then discussing them), but also specific linguistic features. Our goal is to study coreference chains (all the expressions of a text that refer to the same extra-linguistic entity) in a corpus of French IMRAD articles (5 texts, 32,539 words). We show that different types of chains have specific features and that they cannot be studied without distinction. We first categorize chains by the type of their referent and analyze in particular three of these types: author(s), abstract concepts and groups. We then define types of chains by features such as their prominence, their length in the text, the distance between their elements, etc. This dual typology of coreference chains allows us to describe the main types of chains, but also to give a fine-grained analysis of the textual progression in IMRAD articles, especially how and why some referents are present in several sections while others are limited to one section only.